ANALISIS SEKTOR AGRIBISNIS SEBAGAI SEKTOR POTENSIAL YANG BERKELANJUTAN DI KABUPATEN MAGETAN - Febrianty Fauziyah Yauma Wulida; Markus Patiung; Diah Tri Hermawati (Jurnal Ilmiah Sosio Agribis, 2022)
The aims of this study are as follows: to analyze the agribusiness sector as a basic or potential sector in Magetan Regency, to analyze whether the agribusiness sector is a sustainable sector or not in Magetan Regency, to analyze whether the agribusiness sector is a fast-growing and slow-growing sector or a slow-growing advanced sector. slow. This research method uses LQ analysis, DLQ and Klasen Typology analysis. LQ analysis obtained LQ value = 3.34, meaning that the agribusiness sector of Magetan Regency production can meet the needs of the people of Magetan Regency and can even be exported to other regions or abroad, and can prosper the people of Magetan Regency. The DLQ analysis obtained a value of 2.16, meaning that the sector is superior and will remain the basis now and in the future. This shows that the agribusiness sector is a sustainable sector. The comparison between LQ and DLQ produces where LQ = 3.34 while DLQ = 2.16, so that LQ > 1 and DLQ > 1, where the agribusiness sector is the leading sector, meaning that currently the agribusiness sector in Magetan Regency remains the base sector in the present and future. The results of the Klassen typology analysis show the results of rik > ri and yi > yik, where the agribusiness sector is included in the criteria of a fast growing and fast growing sector.Keywords: Agribusiness Sector, LQ, DLQ, Klasen Typology